Implikasi Konsep Fitrah dalam Islam dan Tujuan Pendidikan Nasional - Agus Samsulbassar; Andewi Suhartini; Nurwadjah Ahmad EQ (Program Pascasarjana Universitas Ibrahimy, 2020)
This research aims to determine the implications of the natural disposition concept in Islam for achieving the objectives of National Education. The conclusion of this research shows that teachers will help Indonesian people easily in achieving the goals of National Education when they have understood the natural disposition concept. The education process begins with understanding the natural disposition concept of humans who has a basis, nature, character, and the potential way of working. Three approaches are needed in the educational process. They are the philosophical tauhid approach, chronological approach, and functional approach. This research used a descriptive-analytic appoach with a literature study to examine the natural disposition concept in Islam and its Implications in achieving the objectives of National Education.